2014
DOI: 10.1179/2045772314y.0000000246
|View full text |Cite
|
Sign up to set email alerts
|

Trunk strength and function using the multidirectional reach distance in individuals with non-traumatic spinal cord injury

Abstract: Context: Trunk control is essential to engage in activities of daily living. Measuring trunk strength and function in persons with spinal cord injury (SCI) is difficult. Trunk function has not been studied in non-traumatic SCI (NTSCI). Objectives: To characterize changes in trunk strength and seated functional reach in individuals with NTSCI during inpatient rehabilitation. To determine if trunk strength and seated reach differ between walkers and wheelchair users. To explore relationships between trunk and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…Further refinement of the trunk and abdomen testing paradigm that we created could include paraspinal EMG, and testing for artifacts from nearby structures. A clinical trunk score ( 68 ) and spirometry should be incorporated ( 15 , 162 , 163 ). Another approach to defining a level based on ICs might be to determine the level(s) above which IC spasms cannot be generated.…”
Section: Discussionmentioning
confidence: 99%
“…Further refinement of the trunk and abdomen testing paradigm that we created could include paraspinal EMG, and testing for artifacts from nearby structures. A clinical trunk score ( 68 ) and spirometry should be incorporated ( 15 , 162 , 163 ). Another approach to defining a level based on ICs might be to determine the level(s) above which IC spasms cannot be generated.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in physical function have also been shown to positively impact health behavior and overall QoL as demonstrated by Ginis et al 33 Individuals who are able to reach forward further, as captured by the mFRT, also demonstrate improved seated balance and postural control. 34,35 Ability to reach forward could potentially help conserve energy with everyday tasks, perhaps enabling those with SCI to have increased participation in exercise. Recently Lundström et al, found that aging individuals with SCI had decreased participation in planned exercise secondary to variables including spasticity and decreased strength.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NTSCI state minority among the spinal cord population. NTSCI can be a consequence of multiple etiologies including infection, spinal stenosis, vascular impairment, transverse myelitis, syringomyelia, malignant and benign tumors [ 2 ]. Traumatic spinal cord injury results from contusion, compression, and stretch of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%